A simplified version of rapid susceptibility testing of bacteria and yeasts using optical nanomotion detection - Villalba, Maria I.; Gligorovski, Vojislav; Rahi, Sahand J.; Willaert, Ronnie G.; Kasas, Sandor (Frontiers in Microbiology, 2024)
We present a novel optical nanomotion-based rapid antibiotic and antifungal susceptibility test. The technique consisted of studying the effects of antibiotics or antifungals on the nanometric scale displacements of bacteria or yeasts to assess their sensitivity or resistance to drugs. The technique relies on a traditional optical microscope, a video camera, and custom-made image analysis software. It provides reliable results in a time frame of 2-4 hours and can be applied to motile, non-motile, fast,